PENGALAMAN REHABILITASI PENYALAHGUNA NARKOTIKA DI PANTI REHABLIITASI INABAH XIX SURABAYA - Firdaus, Modayosi Laillatussyradj (Paradigma, 2021)
Victims of illicit drug trafficking or who are later referred to as abusers are one of the social problems that need special handling both legally and socially. One of the treatments that need to be done is to bring victims of drug abusers into drug rehabilitation centers. The location of this research is the Inabah XIX Surabaya Foundation. This location was chosen because the rehabilitation unit uses a rehabilitation method with an "Islamic" religious approach. The object of study in this research is the conscious experience and meaning contained in the experience of the victim of abuse or the subject of the study after undergoing the rehabilitation process. The main purpose of this research is to reveal the meaning of rehabilitation in consciousness after undergoing rehabilitation. This study uses a qualitative method with a phenomenological approach. The theoretical perspective used in this study is Edmund Husserl’s Phenomenology with a descriptive phenomenological model developed by Amedeo Giorgi. The subjects of this study were selected purposively, namely patients who underwent rehabilitation within a minimum of five months. The results of this study indicate that each subject has a unique unit of experience individually. so that the meaning that is raised by the research subject as an individual unit can be varied. As in this study. There are research subjects who interpret the rehabilitation process that has been carried out as reintroducing themselves to God through routine worship, there are also subjects who interpret the rehabilitation process as a form of increasing religious awareness in worship and using this as an encouragement to be able to deepen the knowledge of the religion "Islam". Keywords: Experience, Awareness, Meaning, Phenomenology, Abusers, Narcotic